2022
DOI: 10.5614/j.eng.technol.sci.2022.54.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Powdered Activated Carbon (PAC)-Ceramic Composite Adsorbent for Iron and Aluminum Cations Removal from Acid Mine Drainage

Abstract: Acid mine drainage has become a serious problem globally, polluting groundwater with heavy metals. Adsorption is considered a simple and effective approach to addressing this emerging issue. A commonly used adsorbent is powdered activated carbon (PAC), but this is susceptible to being washed into the waste stream, either during or after the adsorption process due to its low density. This research combined PAC with clay that was molded into small clay balls (~1 cm in diameter) then baked at a very high temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The full set of helium equilibrium data points is used to calculate the dead volume and create Figure 4. Equations ( 8), (9), and (10) were used to create the plot for the specific adsorption of propane shown in Figure 5. Propane data at 30°C 8 bar had been gathered but was found to have procedural error and was removed from the data set.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full set of helium equilibrium data points is used to calculate the dead volume and create Figure 4. Equations ( 8), (9), and (10) were used to create the plot for the specific adsorption of propane shown in Figure 5. Propane data at 30°C 8 bar had been gathered but was found to have procedural error and was removed from the data set.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the methane study are shown in Figure 1. Current uses of activated carbon include filtration to create drinking water, ingestion to treat poisoning by preventing the uptake of poisons into the victim, treating air pollution, and purifying other liquids and gases [4], [5], [6], [7], [8], [9]. The high surface area of activated carbon allows it to perform well in these filtration and extraction roles based on its adsorptive capabilities.…”
Section: Introductionmentioning
confidence: 99%